2023
DOI: 10.3390/w15142517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carrying Capacity and Obstacle Factors of Water Resources in Longnan City, China, Based on Driving–Pressure–State–Response and Technique for Order Preference by Similarity to an Ideal Solution Models

Abstract: Measuring the carrying capacity of water resources and identifying obstacle factors are critical prerequisites for the rational allocation of regional water resources and the high-quality development of economic society. This study took Longnan City, a typical city in northwest China with abundant water resources but an underdeveloped economy, as the research object. Based on the DPSR (Driving–Pressure–State–Response), an evaluation indicator system was constructed. TOPSIS (Technique for Order Preference by Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Results for the first hypothesis are mixed in different contexts, as, it was accepted in the central and east region of China, however, drivers for high quality development in manufacturing industry have least role in influencing pressure in the west region. The results for the first hypothesis are similar to the Dang et al (2023) which shows that changes in the driving forces causes a significant change in pressure in the carrying capacity of water resources in Longnan city of China; However, contradict with the results of Ren et al (2022) which describe that major driving forces of ecosystem health including natural and economic factors can increase or decrease the pressure on ecosystem health. Findings in the study of J.-Y.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…Results for the first hypothesis are mixed in different contexts, as, it was accepted in the central and east region of China, however, drivers for high quality development in manufacturing industry have least role in influencing pressure in the west region. The results for the first hypothesis are similar to the Dang et al (2023) which shows that changes in the driving forces causes a significant change in pressure in the carrying capacity of water resources in Longnan city of China; However, contradict with the results of Ren et al (2022) which describe that major driving forces of ecosystem health including natural and economic factors can increase or decrease the pressure on ecosystem health. Findings in the study of J.-Y.…”
Section: Resultscontrasting
confidence: 60%
“…Wei et al (2019) showed a similar pattern where major driving forces of enterprises energy efficiency including technological innovation, society, natural reserves, corporate environmental concern, and investment in R&D. Findings for hypothesis 2 are significant for all regions in China which shows that pressure influences state significantly. Findings from the study of Dang et al (2023) are not so different which show that pressure for carrying capacity of water resources significantly influence the state to take necessary actions. Further, results show a similar pattern with the study of Ren et al (2022) which describe that change in eco-system pressure significantly influence the eco-system state.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the water resource endowment of each province and urban area in the region is quite different. Although the total amount of water resources in northwestern China is large, the amount of water resources per capita is small, and a large amount of ecological water is polluted [6,7]. Therefore, there is a severe water deficit in the local area.…”
Section: Introductionmentioning
confidence: 99%